Chromosome 1 trisomy confers resistance to aureobasidin A in Candida albicans - Zheng, Lijun; Xu, Yi; Dong, Yubo; Ma, Xiaowen; Wang, Chen; Yang, Feng; Guo, Liangsheng (Frontiers in Microbiology, 2023)
Candida albicans is a prevalent opportunistic human fungal pathogen. However, there are currently very few antifungal treatments available. Inositol phosphoryl ceramide synthase is an essential and fungal-specific protein that also provides a novel and promising antifungal target. Aureobasidin A is a widely used inhibitor of inositol phosphoryl ceramide synthase, however the mechanism of resistance to aureobasidin A is largely unknown in pathogenic fungi. Here we investigated how C. albicans adapted to low and high concentrations of aureobasidin A. We identified trisomy of chromosome 1 as the predominant mechanism of rapid adaptation. Resistance to aureobasidin A was unstable because of the inherent instability of aneuploids. Importantly, chromosome 1 trisomy simultaneously regulated genes which were associated with aureobasidin A resistance that are on this aneuploid chromosome as well as on other chromosomes. Furthermore, the pleiotropic effect of aneuploidy caused altered resistance not only to aureobasidin A but also to other antifungal drugs including caspofungin and 5-flucytosine. We posit aneuploidy provides a rapid and reversible mechanism of development of drug resistance and cross resistance in C. albicans.